Human Resource Development Strategy to Improve Employee Performance at Wirman Sambal Business: Building a High-Performance Team - Gusti Ayu Zetty Andani; Harnida Wahyuni Adda; Idris; Suryadi Samudra (PT. Global World Scientific, 2024)
This study aims to analyze the Human Resources (HR) development strategy implemented at Wirman Sambal Business to enhance employee performance and foster a high-performance team. The dynamic culinary industry requires companies to adapt to rapid market changes, so HR development is a key factor in improving productivity and work quality. Through technical skills training, soft skills development, and mentoring sessions, the company strives to foster a collaborative work environment and support the enhancement of individual abilities in addressing industry challenges. The results of the study indicate that the HR development strategies implemented at Wirman Sambal, including technical skills training, performance rewards, and collaborative team management, have proven effective in enhancing employee performance and company productivity. The company's revenue has increased significantly, and customer loyalty has also increased. Thus, good HR management makes a significant contribution to the company's long-term success.